2007
DOI: 10.1016/j.physc.2007.04.218
|View full text |Cite
|
Sign up to set email alerts
|

Angular dependence of upper critical field in two-band Ginzburg–Landau theory

Abstract: Generalization of two-band Ginzburg-Landau (GL) theory to the case of anisotropic mass is presented. The temperature dependence of the anisotropy parameter of upper critical field c c2 ðT Þ ¼ H k c2 ðT Þ=H ? c2 ðT Þ and angular dependence of H c2 (h, T) are calculated using anisotropic mass two-band Ginzburg-Landau theory of superconductors. It is shown that, with decreasing temperature anisotropy parameter c c2 (T) is increased. Results of our calculations are in agreement with experimental data for single cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The increase of the critical field approaching θ = 0 • and θ = 90 • invites a comparison with the cusp-like angle dependence of the critical field for surface superconductivity H c3 (21). We A B Fig.…”
Section: Fig 2 (A)mentioning
confidence: 75%
See 1 more Smart Citation
“…The increase of the critical field approaching θ = 0 • and θ = 90 • invites a comparison with the cusp-like angle dependence of the critical field for surface superconductivity H c3 (21). We A B Fig.…”
Section: Fig 2 (A)mentioning
confidence: 75%
“…This description has been widely applied to describe two-band superconductivity, including for MgB 2 (28) and NbSe 2 (29). We note that Askerzade and Tanatar (21) give a phenomenological analytic expression for H c2 (θ ) in a twoband model that includes a gradient coupling term. Even setting the gradient coupling parameter in their expression to zero, parameters can be chosen that give an excellent fit to our H c2 (θ ) data.…”
Section: Fig 2 (A)mentioning
confidence: 99%
“…It has been shown that a single band anisotropic model can properly describe the angular dependence of 2 ( ) in a multiband system near [21]. Similarly, the current model/theory can be applied to 1111-family of iron based two-band superconductor…”
Section: Calculation Of Upper Critical Magnetic Fieldmentioning
confidence: 98%
“…T * . In our recent work [36] we introduced effective masses in different bands with angular dependence. In layered anisotropic superconductors the effective masses are tensor quantities.…”
Section: Hck εRmentioning
confidence: 99%